Integrating Chinese medicine into mainstream cancer therapies: a promising future - Ni, Baoyi; Xue, Kaiyuan; Wang, Jia; Zhou, Jilai; Wang, Lankang; Wang, Xinmiao; Liu, Ting; Ye, Naijing; Jiang, Jiakang (Frontiers in Oncology, 2024)
Malignant tumors are complex systemic chronic diseases and one of the major causes of human mortality. Targeted therapy, chemotherapy, immunotherapy, and radiotherapy are examples of mainstream allopathic medicine treatments that effective for intermediate and advanced malignant tumors. The ongoing use of conventional allopathic medicine has resulted in adverse responses and drug resistance, which have hampered its efficacy. As an important component of complementary and alternative medicine, Chinese medicine has been found to have antitumor effects and has played an important role in enhancing the therapeutic sensitivity of mainstream allopathic medicine, reducing the incidence of adverse events and improving immune-related functions. The combined application of adjuvant Chinese medicine and mainstream allopathic medicine has begun to gain acceptance and is gradually used in the field of antitumor therapy. Traditional natural medicines and their active ingredients, as well as Chinese patent medicines, have been proven to have excellent therapeutic efficacy and good safety in the treatment of various malignant tumors. This paper focuses on the mechanism of action and research progress of combining the above drugs with mainstream allopathic medicine to increase therapeutic sensitivity, alleviate drug resistance, reduce adverse reactions, and improve the body’s immune function. To encourage the clinical development and use of Chinese herb adjuvant therapy as well as to provide ideas and information for creating safer and more effective anticancer medication combinations, the significant functions of Chinese herb therapies as adjuvant therapies for cancer treatment are described in detail.